2011
DOI: 10.1007/s10959-011-0383-2
|View full text |Cite
|
Sign up to set email alerts
|

The Semicircle Law for Matrices with Independent Diagonals

Abstract: We investigate the spectral distribution of random matrix ensembles with correlated entries. We consider symmetric matrices with real valued entries and stochastically independent diagonals. Along the diagonals the entries may be correlated. We show that under sufficiently nice moment conditions the empirical eigenvalue distribution converges almost surely weakly to the semi-circle law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 6 publications
2
40
0
Order By: Relevance
“…In particular, in Friesen and Löwe (2013a) it was shown that there is a phase transition: If the correlation of the exchangeable random variables go to 0, the limit of the ESD is the semi-circle law, while otherwise it can be described in terms of a free convolution of the semi-circle law with a limiting law obtained in Bryc et al (2006). In this note we will answer a question by C. Deninger (private communication) and extend the results from Friesen and Löwe (2013a) and Friesen and Löwe (2013b) to ergodic sequences of random variables. We will see that the convergence of the ESD only depends on the correlations of the entries.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…In particular, in Friesen and Löwe (2013a) it was shown that there is a phase transition: If the correlation of the exchangeable random variables go to 0, the limit of the ESD is the semi-circle law, while otherwise it can be described in terms of a free convolution of the semi-circle law with a limiting law obtained in Bryc et al (2006). In this note we will answer a question by C. Deninger (private communication) and extend the results from Friesen and Löwe (2013a) and Friesen and Löwe (2013b) to ergodic sequences of random variables. We will see that the convergence of the ESD only depends on the correlations of the entries.…”
Section: Introductionmentioning
confidence: 54%
“…The ideas in the first section of the proof partially follow Friesen and Löwe (2013b) which in turn are based on considerations in Schenker and Schulz-Baldes (2005). For the reader's convenience and since we will need the arguments for the second part of the proof as well, we will illustrate the main steps.…”
Section: Proof Of Theorem 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Friesen and Löwe [18] consider matrix ensembles with independent diagonals generated by a sequence Y n of weakly correlated random variables. In their case the limit distribution is the semicircle law again.…”
Section: Decaying Correlationsmentioning
confidence: 99%
“…A different approach to universality was taken in [16], [11] and [9]. In all these articles random matrices with correlated entries are studied.…”
Section: Introductionmentioning
confidence: 99%